The Use of Essential Oils as Rumen Modifier in Dairy Cows - Dewi Ayu Ratih Daning; C Hanim; B P Widyobroto; L M Yusiati (Indonesian Center for Animal Research and Development, 2020)
Feed efficiency is essential for dairy cows because it can increase production and quality of milk, and reduce methane emissions in the environment. One of the strategies on increasing feed efficiency is using rumen modifier. Essential oils have antimicrobial activities and have been used in rumen modifier in dairy cows. The aim of this paper is to review several studies on the utilization of essential oils as feed additive to enhance production and quality of milk of dairy cow. Based on some research reports, using essential oils which contained thymol, eugenol, cinnamaldehyde and carvacrol in dairy cattle feed decreased the population of protozoa, methanogens, proteolytic, and biohydrogenase bacteria. The impact of engineering of the rumen microbial population has led to optimal rumen fermentation resulted in the efficiency of carbohydrate, protein, and fat utilizations. It can be concluded that essential oils are potential as rumen modifier by inhibit methanogenesis, increase propionate, energy efficiency and ruminal by pass protein. The inconsistent results on milk production and milk fat requires further research to study deeper the effect of dosage and type of essential oils on dairy cows performance.